Industrial Relations Education in Canada: The Perspective of Vocational/Technical Educators - Fraser, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
This paper discusses the relevancy of industrial relations education in the formal education Systems in Canada, and through analysis of a survey of vocational and technical educators, examines their perceptions of IR education in Canada generally, and in vocational/technical institutions specifically.